Multi-step method for determining the energy spectrum of different quantum potential wells - Lopez Villamil, Ramon Eduardo; Pérez Castro, I.; Zapata de la Cruz, M. A.; Tiscareño Ramirez, J. (JOURNAL OF BASIC SCIENCES, 2024)
In this work, the bound states of a quantum system with a triangular potential well are numerically determined. Additionally, a practical case is studied in which a potential found in MOSFET devices is analyzed. In both cases, the multi-step approximation method is used, which involves approximating the potential by a chain of n-step potentials. From this new potential, the expressions for the reflection and transmission coefficients are determined through a recursive formula, which is a generalization of the coefficients for the simple step potential case. For the system with a triangular well, two bound energies are found with relative errors of less than 1%, while for the potential associated with MOSFET devices, only one bound energy is obtained
Keywords: Multi-step; Potential well; Schrödinger equation; Bound states; MOSFET